The Last of the Line - Weigall, Charles Harvey, 1794-1877; Hall, S. C., Mrs., 1800-1881 (1840)
Duel scene from the story 'Last of the Line' from 'Sketches of Irish Character'.
Title inscribed l.c. on sheet.
Attributed to Charles Harvey Weigall.
Catalogue of Irish Topographical Prints and Original Drawings / Rosalind M. Elmes ; New edition revised and enlarged by Michael Hewson - Dublin : Malton Press, 1975
Ireland: its scenery, character, &c / Mr. & Mrs. S. C. Hall - London: How and Parsons, 1841-43.
Sketches of Irish character
Keywords: Dueling -- Ireland -- 19th century; Pencil drawings -- Irish -- 1830-1840.